Troubleshooting the extrusion process : a systematic approach to solving plastic extrusion problems - Noriega E., Maria del Pilar; Rauwendaal, Chris J., 1950- (Hanser Publishers ; Hanser Publications, 2019)
"Troubleshooting extrusion problems is one of the most challenging tasks in extrusion operations, requiring a good understanding of the extrusion process and the material properties, good instrumentation, good analysis tools, and a systematic and logical approach. This book addresses all issues crucial in extrusion troubleshooting. Includes industrial case studies, richly illustrated with photographs and photomicrographs, used to provide exemplary approaches to efficient problem analysis and problem solving. The interconnectivity between the different relevant knowledge areas such as materials engineering, processing technology, and product development is emphasized. The third edition comprises a very significant update, with around 50% more content, especially focusing on additional case studies"--
Keywords: plasty; vytlačování plastů; plastics; plastic extrusion; monografie; případové studie; monographs; case studies